2015
DOI: 10.5901/mjss.2015.v6n1s3p435
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Factors Affecting Employee Innovative Behavior

Abstract: The research analyzed employers innovative behavior of the organization and importance of influencing factors on it. As research methods were chosen method of structured interrogation, the method of pairwise comparisons, expert evaluation and correlation and regression analysis. The research results were gender difference in innovative employer behavior: more favorable innovation perception in woman -57%, in men -43%, the majority of an active reformers (willing, able to work and active), found among female wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Secondly, the student age contains significant reserves for the natural inclusion of young people in socializing situations of knowledge, communication, creativity, development of new activities, new relationships and new social spaces, ensuring the full disclosure of the individual-special in the context of social and social. The specificity of the student's age is that there is an expansion of the living space of the individual (the diversity of the circle of communication, the diversity of social relations and relationships, the accumulation of a range of social knowledge, norms and methods of social interaction); intensively tested various social roles through the inclusion of students in active labor and social activities, provided awareness of their goals, life aspirations, development of the life plan [7,8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the student age contains significant reserves for the natural inclusion of young people in socializing situations of knowledge, communication, creativity, development of new activities, new relationships and new social spaces, ensuring the full disclosure of the individual-special in the context of social and social. The specificity of the student's age is that there is an expansion of the living space of the individual (the diversity of the circle of communication, the diversity of social relations and relationships, the accumulation of a range of social knowledge, norms and methods of social interaction); intensively tested various social roles through the inclusion of students in active labor and social activities, provided awareness of their goals, life aspirations, development of the life plan [7,8,9].…”
Section: Resultsmentioning
confidence: 99%
“…A serious influence is exerted by the psychological microclimate, formed by the management (Idris et al, 2015). Ideally, it will not only reduce the level of stress, but will also increase the involvement of employees in the innovation activities and increase their innovative activity (Kabasheva et al, 2015;Oosenbrug, 2015;Palmer et al, 2015;Skobleva et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Leonga and Rasli [57] did not find a significant difference between gender and innovative business behavior. Kabasheva et al [58] found that women's perception of innovation is more appropriate than that of men. The present study also supports the results of this research.…”
Section: Discussionmentioning
confidence: 99%